Innovation Performance of Nursing: Competence, Motivation and Organizational Commitment as Mediating - Saryadi; Liss Dyah Dewi Arini; Asri Maharani (TIJAB (The International Journal of Applied Business), 2023)
Background: Attention to open innovation is more important for future research. The impact of the globalization era in health care means that nursing staff are required to be competitive and more professional with the use of increasingly developing technology. Innovation performance is an important determinant of organizational success. Objective: The substantial for this study is analysing key factors which effect the relationship between competence, motivation to innovate the performance of nursing with organizational commitment as mediating. Method: This research adopted cross-sectional research. The total respondents in this study was 60 nurses at Jasmine Room RSST Klaten with a census. This study used a hypothesis for applying path analysis, validity reliability for questioner, Statistic-test, and also coefficient determination with correlation. Results: Path 1 show that competence (Co) and motivation (Mt) have positive significance on organizational commitment (Z).  Path 2 shows that competence (Co), motivation (Mt), and organizational commitment (Z) have positive significance. Highlighting the findings, nurse behaviour in innovation is based on competence. The support of hospital organizational commitment has an impact on strengthening nurses' ability in innovation behaviour. Improving the behaviour of nursing personnel in innovating will realize public health needs, and the need for understanding in healthy behaviour. In nursing staff, both those at a young or old age who will retire, competence becomes a factor that cannot be ruled out by funds to innovate. For the motivation, it does not have much meaning for nursing personnel who are old and about to retire. Conclusion: The spotlight on findings shows the behaviour of nurses in innovation is based on competence. The support of hospital organizational commitment has the impact of strengthening the ability of nurses in innovation behaviour. Increasing the behaviour of nursing personnel in innovating will realize public health needs, and the need for understanding healthy behaviour. Keywords: Innovation performance, multicultural competence, motivation, organizational commitment.